Efficient Sufficiency: A qualitative evaluation of a 1 year pilot study of young people and parents accessing a mental health drop‐in centre in a paediatric hospital. (5th September 2022) - Catanzano, Matteo; Bennett, Sophie D.; Fifield, Kate; Xu, Laila; Sanderson, Charlotte; Coughtrey, Anna E.; Kerry, Ellie; Liang, Holan; Heyman, Isobel; Shafran, Roz
Abstract: Background: Children and young people with long‐term physical health conditions (LTC) are known to have higher levels of co‐morbid mental health problems than medically healthy children. Evidence‐based treatments for mental health problems are effective in children who also have an LTC. This study aimed to explore the factors associated with participants' perceived acceptability and impact of a transdiagnostic mental health centre offering brief psychological assessment and treatment for children and young people and/or their families with mental health needs in the context of long term physical conditions. Methods: One‐hundred twenty‐eight patients attending the drop‐in centre were invited to participate. Overall, 35 participated (31 parents/carers; 4 children and young people) in semi‐structured interviews (either in person or by phone) exploring their experience of the centre. Interviews were audio‐recorded, transcribed and checked. Framework analysis was then conducted on all transcripts. Results: Overall, participants found the drop‐in centre highly acceptable and reported a positive experience. Reasons for this varied but broadly focused around four themes: (1) efficient sufficiency; (2) autonomy; (3) fusion of process and content factors and (4) (dis)parities of esteems and 'seeing both sides of the coin'. Conclusions: Participants found the intervention acceptable. A mental health drop‐in centre in a paediatric hospital appears to be a positive and valued adjunct to supplement existing mental health services.